TAQMAN-BASED DUPLEX REAL-TIME POLYMERASE CHAIN REACTION APPROACH FOR THE DETECTION AND QUANTIFICATION OF DONKEY AND PORK ADULTERATIONS IN RAW AND HEAT-PROCESSED MEATS - Kesmen, Zulal; Gulluce, Ayten; Yilmaz, Mustafa T.; Yetiman, Ahmet E.; Yetim, Hasan (TAYLOR & FRANCIS INC, 2014)
In this study, a rapid and highly specific TaqMan-based duplex real-time polymerase chain reaction method, based on the simultaneous amplification of fragments of the mitochondrial ND2 and ND5 genes, was developed and optimized for the identification and quantification of pork and donkey meats in raw and cooked binary donkey/beef and pork/beef mixtures. Accumulation of polymerase chain reaction products was monitored by measuring the fluorescent signals from FAM and HEX labeled probes specific for pork and donkey, respectively. As a consequence, target meat species could be detected at a level of 0.001% in raw and oven-cooked meat mixtures, and at a level of 0.01% in autoclaved meat mixtures. The result in this study indicated that the TaqMan-based duplex polymerase chain reaction assay could be successfully used in the identification and quantification of donkey and pork in adulteration studies with a high degree of specificity and sensitivity.
Keywords: Species identification; Duplex real-time polymerase chain reaction; TaqMan probe; Raw and cooked meat products; Meat adulterations; SPECIES-SPECIFIC DNA; HORSE MEAT; QUANTITATIVE DETECTION; PCR; IDENTIFICATION; FOOD; PRODUCTS; BEEF; CHICKEN; SHEEP; Food Science & Technology